Environmental justice in the context of urban green space availability, accessibility, and attractiveness in postsocialist cities. (November 2020) - Kronenberg, Jakub; Haase, Annegret; Łaszkiewicz, Edyta; Antal, Attila; Baravikova, Aliaksandra; Biernacka, Magdalena; Dushkova, Diana; Filčak, Richard; Haase, Dagmar; Ignatieva, Maria; Khmara, Yaryna; Niţă, Mihai Razvan; et al.
Abstract: This article aims to position postsocialist cities in Central and Eastern Europe in the broader debate on urban environmental justice. The article crosscuts through all three dimensions of justice (distributive/distributional, procedural/participatory, and interactional/recognition) in the context of urban green and blue space provision. Environmental justice is still an emerging topic in postsocialist cities, constrained by market-orientation and neoliberal trends within society, privatization, and the primacy of private interests. The respective situation in postsocialist cities provides insights into the international debate on environmental justice, by highlighting some extremes related to neoliberal and populist governments and very rapid processes that lack long-term democratic consensus within societies. The findings of this study are discussed in the context of a postsocialist legacy, which includes broad tolerance for inequalities, a lack of solidarity in society, a lack of responsibility for the public interest, and extreme individualization and disregard for social interests. This has gradually led to the corporatization of local authorities and various business–government coalitions. This setting is more likely to favor business models related to the use and management of urban green and blue spaces than the environmental justice discourse. Highlights: Broad tolerance for inequalities, lack of solidarity in society, lack of responsibility for the public interest Extreme individualisation and disregard for the social interest Corporatisation of local authorities and various business–government coalitions Urban green and blue spaces poorly considered in planning Justice consideration far from being accepted as guiding principles for urban greening